Much ado about baseball - LaRocca, Rajani (Yellow Jacket, 2021)
Loosely based on Shakespeare's "Much Ado About Nothing," twelve-year-olds Trish and Ben should be automatic friends because they both play baseball on a Little League team in Comity, Massachusetts, and they both love solving math puzzles, but obstacles stand in their way.